TRANSPARANSI DAN AKUNTABILITASPENGELOLAAN DANA DESA T.A. 2018 DI KECAMATAN PALAKKA MENURUT PERSPEKTIF KEUANGAN PUBLIK ISLAM - Herianti Herianti; Arifin S. (Institut Agama Islam Negeri (IAIN) Bone, 2020)
Abstract This study discusses transparency accountability in the management of the Village Fiscal Fund 2018 in the District of Palakka Bone Regency and aims to find out 1) What forms of transparency and accountability in the management of the Village Fund, 2) What is the impact of transparency accountability in the management of the Village Fund on village development and 3) How is the perspective Islamic public finance to the level of transparency accountability in the management of the Village Fund. This type of research is qualitative by using a sociological approach. The results showed that 1) Transparency accountability of the village government in Palakka sub-district was transparent accountable, although not yet fully optimal. The form of transparency is through the installation of transparency boards and activity information boards, as well as accountability in the form of accountability for the use of the budget. 2) The impact of the management of the fund is the development of strategic infrastructure and the development of community economic activities through empowerment. 3) Village Funds as a public fund in the perspective of Islamic public finance are based on the concept of the benefit of the people without departing from Islamic values both in terms of income and from the expenditure process. As reality in the field with a lot of assistance to the village government social security provided reflects that the Village Fund as a public fund has been fulfilled as in the Islamic concept although still limited by regulations.AbstrakPenelitian ini membahas tentang transparansi akuntabilitas pengelolaan Dana Desa T.A 2018 di Kec. Palakka Kab. Bone dan bertujuan Untuk mengetahui 1) Bagaimana bentuk transparansi dan akuntabilitas pengelolaan Dana Desa, 2) Bagaimana dampak transparansi akuntabilitas pengelolaan Dana Desa terhadap pembangunan desa dan 3) Bagaimana persfektif keuangan publik islam terhadap tingkat transparansi akuntabilitas pengelolaan Dana Desa. Jenis penelitian yang digunakan adalah kualitatif dengan menggunakan pendekatan sosiologis. Hasil penelitian menunjukkan bahwa 1) Transparansi akuntabilitas pemerintah Desa di Kecamatan Palakka sudah transparan akuntabel meskipun belum sepenuhnya maksimal. Bentuk transparansinya adalah melalui pemasangan papan transparansi dan papan informasi kegiatan, serta akuntabilitasnya dituangkan dalam bentuk pertanggung-jawaban penggunaan anggaran. 2) Dampak dari tata kelola dana tersebut adalah adanya pembangunan infrastruktur yang strategis dan pengembangan kegiatan ekonomi masyarakat melalui pemberdayaan. 3) Dana Desa sebagai dana publik dalam persfektif keuangan publik Islam adalah didasarkan pada konsep kemaslahatan umat tanpa keluar dari nilai-nilai Islam baik itu dari sisi perolehan pendapatannya maupun dari proses belanjanya. Sebagaimana realita dilapangan dengan banyaknya bantuan hingga penjaminan sosial pemerintah desa yang diberikan mencerminkan bahwa Dana Desa sebagai dana publik telah terpenuhi segaimana dalam konsep islam meskipun masih dibatasi oleh regulasi.